Reng Lake’ Noro’ Reng Bini’ Culture in the Perspective of Islamic Epistemology and Local Wisdom - Prasetyo Nugroho; Akh Lutfi; Moh Farid; Fahmi Ashar; Sutikno Sutikno; Muhammad Alkirom Wildan (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study examines the cultural practice of Reng Lake' Noro' Reng Bini' in Madurese society from the perspectives of Islamic epistemology and local wisdom, particularly in relation to male migration and women's post-marital security. The research employs a qualitative descriptive-analytical method using anthropological, phenomenological, and normative-theological approaches. Data were collected through in-depth interviews with religious leaders, village elders, and families practicing the tradition, supported by document analysis of classical fiqh texts, Qur'anic exegesis, and reputable journal articles. Data analysis involved data reduction, thematic coding, hermeneutic interpretation, and source triangulation. The findings indicate that Reng Lake' Noro' Reng Bini' functions as a cultural-religious strategy to protect women, adapt to male migration, and locally reinterpret the concept of qiwāmah. This study concludes that Madurese local wisdom operates as a practical form of Islamic epistemology, offering theoretical contributions to Islamic family studies and practical implications for culturally responsive Islamic discourse and family policy.